2023
DOI: 10.3390/cimb45040227
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of the Brain Endothelium

Abstract: The blood–brain barrier (BBB) is part of a neurovascular structure located in the brain’s micro vessels, that is essential to maintain brain homeostasis, but prevents the brain uptake of most drugs. Because of its importance in neuro-pharmacotherapy, the BBB has been the subject of extensive research since its discovery over 100 years ago. Major advances in understanding the structure and function of the barrier have been made. Drugs are re-designed to cross the BBB. However, despite these efforts, overcoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
(109 reference statements)
0
0
0
Order By: Relevance
“…shown by the latter studies, inhibiting efflux transporters by probenecid markedly increases bumetanide brain levels. Transporters involved in the uptake and efflux of drugs at the BBB are not homogeneously expressed at the BBB of different brain regions (Alnaqbi et al, 2023;Villabona-Rueda et al, 2019;Zhao & Pollack, 2009), which thus likely add to the heterogeneous brain distribution of bumetanide following systemic administration in rats observed here.…”
Section: Active Transport Of Bumetanide At the Bloodbrain Barriermentioning
confidence: 79%
See 1 more Smart Citation
“…shown by the latter studies, inhibiting efflux transporters by probenecid markedly increases bumetanide brain levels. Transporters involved in the uptake and efflux of drugs at the BBB are not homogeneously expressed at the BBB of different brain regions (Alnaqbi et al, 2023;Villabona-Rueda et al, 2019;Zhao & Pollack, 2009), which thus likely add to the heterogeneous brain distribution of bumetanide following systemic administration in rats observed here.…”
Section: Active Transport Of Bumetanide At the Bloodbrain Barriermentioning
confidence: 79%
“…The regional differences in bumetanide brain levels reported here are likely related to the regional heterogeneity of the BBB (Löscher & Friedman, 2020;Villabona-Rueda et al, 2019;Wilhelm et al, 2016), regional differences in drug transporters (Alnaqbi et al, 2023;Villabona-Rueda et al, 2019;Zhao & Pollack, 2009), and regional differences in capillary density and perfusion rate (Beck & Krieglstein, 1987;Horton et al, 1980;Zhao & Pollack, 2009). Zhao and Pollack (2009) reported that the regional perfusion flow rate varies 7.5-fold, and capillary density (based on vascular volume) varies 3.7-fold, across 13 brain regions (olfactory bulb, striatum, hippocampus, frontal cortex, parietal cortex, occipital cortex, superior and inferior colliculi, hypothalamus, thalamus, midbrain, pons, medulla, and cerebellum) examined in the mouse.…”
Section: Heterogeneous Local Cerebral Blood Flowmentioning
confidence: 87%
“…These will need to have wellestablished molecular and cellular mechanisms of action, including carrier ligand-cell surface receptor [184][185][186][187][188][189]281] interactions, as well as clearly characterized in vivo behavior [191][192][193]. The latter encompasses possible crossing of the blood-brain barrier via transcytosis [282][283][284][285][286], as well as local drug delivery through stereotactic approaches. Furthermore, non-invasive monitoring of therapeutic drug function in patients is highly desirable.…”
Section: Unsolved Challenges and Novel Therapeutic Approaches Guided ...mentioning
confidence: 99%
“…Anatomical barriers against nanoparticle or vector-based therapeutics: One study [291] reported that a particular serotype, AAV9, is capable to cross the blood-brain barrier (BBB) [286,297], raising the possibility of intravascular administration as a non-invasive delivery route to achieve widespread CNS gene expression (Figure 7). Crossing of the bloodbrain barrier appears to occur via transcytosis [282][283][284][285]. Notably, this same AAV serotype is also capable to enter the myocardium across the tight cardiovascular endothelium (impermeable for other AAV serotypes) and has previously been successfully employed for cardiac gene transfer [258,293] and the first demonstration of cardiac RNA interference (RNAi) therapy [93].…”
Section: Unsolved Challenges and Novel Therapeutic Approaches Guided ...mentioning
confidence: 99%